First‐Principles Study of Metal Atoms Adsorption on 2D Dumbbell C4N. Issue 1 (30th September 2019) - Xu, Min; Wang, Hongyan; Sun, Songsong; Li, Hengtao; Li, Xiumei; Chen, Yuanzheng; Ni, Yuxiang
Abstract : Similar to graphene, zero bandgap is found in the recently proposed 2D dumbbell C4 N (DB C4 N), which limits its applications as electronic devices. Surface adsorption effectively modifies the electronic and magnetic properties of the 2D materials. Herein, the adsorption behaviors of 16 metal atoms adsorbed on the DB C4 N, including alkali metals, alkaline earth metals, 3 d transition metals (TMs), and precious metals, are investigated using the density functional theory. The electronic and magnetic properties of the adatom–C4 N systems are systematically explored by analyzing the adsorption energies, the density of states (DOS), the band structures, the charge transfer, the total magnetic moments, the work function, and the dipole moment. It is revealed that the alkali metals (Li, Na), alkaline‐earth metals (Be, Mg), 3 d TMs (Ti, V, Cr, Mn, Fe, Co), and precious metals (Ag, Pt, Au) open the zero bandgap of DB C4 N via charge transfer between the adatoms and the DB C4 N surface. Moreover, the 3 d transition and precious metals adatoms induce magnetism in the monolayer C4 N. These results qualify the metal‐adsorbed C4 N systems as promising candidates for building outstanding electronic and spintronic devices in the future. Abstract : Surface adsorption effectively modifies the electronic and magnetic properties of 2D dumbbell C4 N. The zero bandgap of dumbbell C4 N can be opened via charge transfer between the metal adatoms and the C4 N surface.